Validation of the Dutch-language version of Nurses' Moral Courage Scale - Numminen Olivia; Konings Kasper; Claerhout Roelant; Gastmans Chris; Katajisto Jouko; Leino-Kilpi Helena; de Casterlé Bernadette Dierckx (SAGE PUBLICATIONS LTD, 2025)
Background:
Moral courage as a part of nurses' moral competence has gained increasing interest as a means to strengthen nurses acting on their moral decisions and offering alleviation to their moral distress. To measure and assess nurses' moral courage, the development of culturally and internationally validated instruments is needed.
Objective:
The objective of this study was to validate the Dutch-language version of the four-component Nurses' Moral Courage Scale originally developed and validated in Finnish data.
Research design:
This methodological study used non-experimental, cross-sectional exploratory design.
Participants and research context:
A total of 559 nurses from two hospitals in Flanders, Belgium, completed the Dutch-language version of the Nurses' Moral Courage Scale.
Ethical considerations:
Good scientific inquiry guidelines were followed throughout the study. Permission to translate the Nurses' Moral Courage Scale was obtained from the copyright holder, and the ethical approval and permissions to conduct the study were obtained from the participating university and hospitals, respectively.
Findings:
The four-component 21-item, Dutch-language version of the Nurses' Moral Courage Scale proved to be valid and reliable as the original Finnish Nurses' Moral Courage Scale. The scale's internal consistency reliability was high (0.91) corresponding with the original Nurses' Moral Courage Scale validation study (0.93). The principal component analysis confirmed the four-component structure of the original Nurses' Moral Courage Scale to be valid also in the Belgian data explaining 58.1% of the variance. Confirmatory factor analysis based on goodness-of-fit indices provided evidence of the scale's construct validity. The use of a comparable sample of Belgian nurses working in speciality care settings as in the Finnish study supported the stability of the structure.
Discussion and conclusion:
The Dutch-language version of the Nurses' Moral Courage Scale is a reliable and valid instrument to measure nurses' self-assessed moral courage in speciality care nursing environments. Further validation studies in other countries, languages and nurse samples representing different healthcare environments would provide additional evidence of the scale's validity and initiatives for its further development.